O fim da história ensinada: tecnodocência, currículo e ludoliteracia histórica crítico-significativa para o ensino médio - Sousa Júnior, João Eudes Alexandre de (2023)
In this dissertation, oriented by progressive educational tendencies, are proposing the critical, reflective, and emancipatory use of the artifacts in favor of sociotechnical adequations of the digital technologies to the counter-hegemonical history teaching. This way can stimulate not only individual but also collective and transformative life projects, seeking to assume a technoteaching pedagogical basis, watchful to playfulness and historical materialism. Thus, the student’s autonomy level conferred by the taught history only makes sense if linked to class consciousness, and it is on the basis of this that the intention is to mobilize historical consciousness and develop historical thought. The analytical and propositional construction occurs in face of the relationship between the history taught and the "New" High School: drastic reduction of the classtime; contradictions between formal curriculum documents; lack of structured teaching materials for students; impossibility of financial resources and human (planning time) for schools to produce their own materials. These four points configure the central problem that was sought to be analyzed, explain, and, in the feasible, solved through of the ludoliteracy and historical-critical pedagogy intervention, with the aim of effecting a technoteaching historical literacy for the sake of a dialogical reconstruciomism of the taught history, without avoiding emergent or still current issues of capitalism, such “hyperculturality”, “hyperproductivity”, and their pathologies. To this end, in the analytical dimension, a qualitative-quantitative approach methodology was employed through documentary and bibliographical research, as well as the application of structured and semi-structured questionnaires with high school teachers and students. In the propositional dimension, an approximation to the reconstructivist didactics of history was sought, aiming at proposing a Usable Historical Framework (UHF) through the elaboration of Digital Educational Authorial Materials (MADEs) based on the dialogue of students with primary sources according to the workshop class model. The conceptual repertoire mobilized is fundamentally multidisciplinary and interdisciplinary, resorting to a series of authors who assisted in the perspective analysis of teaching action, highlighting Freire (1996; 1997), Lee (2006; 2016), Barca (2004; 2006), Rüsen (2010; 2014), Marx (2007; 2017), Feenberg (2010; 2011), Schmidt (2020; 2021), Han (2017; 2019), Saviani (1999; 2015), Duarte (2003; 2008), Rancière (2002; 2007), Woodcock (2020), Bey (2004), Zagal (2010), Benjamin (2013), Morozov (2018), Luckesi (2014), Albaine (2019), Lima and Loureiro (2019). Intending a place for the development of taught history in the school environment, it was possible to verify that historical literacy in high school also demands digital literacy. It is concluded that both are potentialized when students have contact with primary historical documents and develop authorial products through playful activities.